2017
DOI: 10.4172/2161-1017.1000262
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Zinc, Magnesium and Selenium among First Trimester Pregnant Saudi Women with Pre-Diabetes and Diabetes

Abstract: Background: Glycosylated hemoglobin (HbA1c) was found to be a valuable predictor of the risk of congenital malformations. Other studies documented diabetic complications in subjects with HbA1c at the pre-diabetic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Hammouda and Mumena [37] and Kutbi et al [38] reported a positive correlation of A1C with TSH and HCY and a negative relation with vitamin B 12 , folate, and vitamin E, in the first-trimester-pregnant Saudi women, observations similar to ours. Along with this, a negative relation was also observed between A1C and minerals such as zinc and selenium in expectant mothers in their first trimester by Hammouda et al [39], also similar to our results. However, there was no information on their plastic usage frequency.…”
Section: Discussionsupporting
confidence: 93%
“…Hammouda and Mumena [37] and Kutbi et al [38] reported a positive correlation of A1C with TSH and HCY and a negative relation with vitamin B 12 , folate, and vitamin E, in the first-trimester-pregnant Saudi women, observations similar to ours. Along with this, a negative relation was also observed between A1C and minerals such as zinc and selenium in expectant mothers in their first trimester by Hammouda et al [39], also similar to our results. However, there was no information on their plastic usage frequency.…”
Section: Discussionsupporting
confidence: 93%